Melatonin Attenuates Neuroinflammation by Down-Regulating NLRP3 Inflammasome via a SIRT1-Dependent Pathway in MPTP-Induced Models of Parkinson’s Disease - Zheng R; Ruan Y; Yan Y; Lin Z; Xue N; Yan Y; Tian J; Yin X; Pu J; Zhang B (Dove Medical Press, 2021)
Ran Zheng, Yang Ruan, Yiqun Yan, Zhihao Lin, Naijia Xue, Yaping Yan, Jun Tian, Xinzhen Yin, Jiali Pu, Baorong Zhang Department of Neurology, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Zhejiang, 310009, People's Republic of ChinaCorrespondence: Baorong Zhang; Jiali PuDepartment of Neurology, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Zhejiang, People's Republic of ChinaFax +86-571-87784752Email brzhang@zju.edu.cn; jialipu@zju.edu.cnBackground: Inflammasome-induced neuroinflammation is a key contributor to the pathology of Parkinson's disease (PD). NLR family pyrin domain-containing 3 (NLRP3) inflammasome activation has been implicated in PD in postmortem human PD brains, indicating it as a potential target for PD treatment. Melatonin, a multitasking molecule, has been found to have anti-inflammatory activities, mediated by silence information regulator 1 (SIRT1). However, whether and how melatonin is involved in inflammasome-induced neuroinflammation in PD pathogenesis remains unclear.Methods: We investigated the potential anti-inflammatory effects of melatonin in vitro and in vivo, using 1-methyl-4-phenylpyridinium (MPP+)-simulated BV2 and primary microglia cell models, and a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced murine PD model, with or without melatonin treatment. Rotarod, grip strength, and open-field tests were performed to measure the effects of melatonin on MPTP-induced motor disorders. Degeneration of dopaminergic neurons was evaluated by immunofluorescence. Changes in microglia were examined by immunofluorescence and Western blotting, and the expression levels of the involved signaling molecules were assessed by Western blotting and enzyme-linked immunosorbent assay (ELISA). Intracellular reactive oxygen species (ROS) was detected using fluorescent probes via flow cytometry.Results: We found that melatonin significantly alleviated motor dysfunction and prevented MPTP-induced neurotoxicity in dopaminergic neurons. Additionally, melatonin reduced MPTP-induced microglial activation and suppressed NLRP3 inflammasome activity, and also inhibited IL-1β secretion. Moreover, in MPP+-primed BV2 cells, melatonin markedly restored the downregulation of SIRT1 and attenuated the activation of the NLRP3 inflammasome. This was reversed by SIRT1 inhibitor treatment.Conclusion: In conclusion, our data demonstrated that melatonin attenuates neuroinflammation by negatively regulating NLRP3 inflammasome activation via a SIRT1-dependent pathway in MPTP-induced PD models. These findings provide novel insights into the mechanism underlying the anti-inflammatory effects of melatonin in PD.Keywords: inflammasomes, melatonin, NLRP3, Parkinson disease, sirtuin 1